Interplay between 4-Hydroxy-3-Methyl-2-Alkylquinoline and N-Acyl-Homoserine Lactone Signaling in a Burkholderia cepacia Complex Clinical Strain - Chapalain, Annelise; Groleau, Marie-Christine; Le Guillouzer, Servane; Miomandre, Aurélie; Vial, Ludovic; Milot, Sylvain; Déziel, Eric (Frontiers in Microbiology, 2017)
Species from the Burkholderia cepacia complex (Bcc) share a canonical LuxI/LuxR quorum sensing (QS) regulation system named CepI/CepR, which mainly relies on the acyl-homoserine lactone (AHL), octanoyl-homoserine lactone (C8-HSL) as signaling molecule. Burkholderia ambifaria is one of the least virulent Bcc species, more often isolated from rhizospheres where it exerts a plant growth-promoting activity. However, clinical strains of B. ambifaria display distinct features, such as phase variation and higher virulence properties. Notably, we previously reported that under laboratory conditions, only clinical strains of the B. ambifaria species produced 4-hydroxy-3-methyl-2-alkylquinolines (HMAQs) via expression of the hmqABCDEFG operon. HMAQs are the methylated counterparts of the 4-hydroxy-2-alkylquinolines (HAQs) produced by the opportunistic human pathogen Pseudomonas aeruginosa, in which they globally contribute to the bacterial virulence and survival. We have found that unlike P. aeruginosa’s HAQs, HMAQs do not induce their own production. However they indirectly regulate the expression of the hmqABCDEFG operon. In B. ambifaria, a strong link between CepI/CepR-based QS and HMAQs is proposed, as we have previously reported increased production of C8-HSL in HMAQ-negative mutants. Here, we report the identification of all AHLs produced by the clinical B. ambifaria strain HSJ1, namely C6-HSL, C8-HSL, C10-HSL, 3OHC8-HSL, 3OHC10-HSL and 3OHC12-HSL. Production of significant levels of hydroxylated AHLs prompted the identification of a second complete LuxI/LuxR-type QS system relying on 3OHC10-HSL and 3OHC12-HSL, that we have named CepI2/CepR2. The connection between these two QS systems and the hmqABCDEFG operon, responsible for HMAQs biosynthesis, was investigated. The CepI/CepR system strongly induced the operon, while the second system appears moderately involved. On the other hand, a HMAQ-negative mutant overproduces AHLs from both QS systems. Even if HMAQs are not classical QS signals, their effect on AHL-based QS system still gives them a part to play in the QS circuitry in B. ambifaria and thus, on regulation of various phenotypes.